Co‐Delivery of Paclitaxel and shMCL‐1 by Folic Acid‐Modified Nonviral Vector to Overcome Cancer Chemotherapy Resistance. Issue 5 (25th January 2021) - Nie, Wen; Wang, Bilan; Mi, Xue; Chen, Jing; Yu, Ting; Miao, Junming; Lin, Yunzhu; Yang, Tingting; Ran, Mengni; Hong, Zehuo; Liu, Xiaoxiao; Liang, Xiao; et al.
Abstract: Acquired chemoresistance presents a major clinical impediment, which is an urgent problem to be solved. Interestingly, myeloma cell leukemia‐1 (MCL‐1) and folate receptor expression levels are higher in chemotherapy‐resistant patients than in pretreatment patients. In this study, a multifunctional folic acid (FA)‐targeting core–shell structure is presented for simultaneous delivery of shMCL‐1 and paclitaxel (PTX). The transfection efficiency of shMCL‐1 with the FA‐targeting delivery system is higher than with a nontargeting delivery system in Skov3 and A2780T cells. The FA‐targeting system significantly inhibits cell growth, blocks cell cycles, and promotes apoptosis of cancer cells in vitro. The mechanisms involved in inhibiting growth are related to Bcl‐2/Bax and cdc2/Cyclin B1 pathways. An analysis of RNA sequencing suggests that shMCL‐1 reverses chemoresistance through regulating genes such as regulator of chromosome condensation 2 (RCC2). The synergetic effect of shMCL‐1 and PTX effectively inhibits tumor growth in both PTX‐resistant and normal cancer models by inducing tumor apoptosis, inhibiting proliferation, and limiting tumor angiogenesis. The study results indicate that a FA‐targeting delivery system combining shMCL‐1 with PTX can simultaneously target tumor sites and restore the sensitivity of chemotherapy‐resistant cancer to PTX. These findings have important implications for patients with normal or PTX‐resistant cancer. Abstract : Nanocomposites reach tumor cells mainly through the blood vessels, recognize the folate receptor of the tumor tissue, and combine with it. Next the nanocomposites enter into the cytoplasm and the lysosome. Lysosomal cleavage interprets paclitaxel and shMCL‐1 plasmid. The plasmid enters the cell nucleus, and shMCL‐1 is translated to silence the MCL‐1 gene to overcome cancer chemotherapy resistance.